2008
DOI: 10.2174/187152708786927877
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Dopamine Transporter in the Action of Psychostimulants, Nicotine, and Other Drugs of Abuse

Abstract: A number of studies over the last two decades have demonstrated the critical importance of dopamine (DA) in the behavioral pharmacology and addictive properties of abused drugs. The DA transporter (DAT) is a major target for drugs of abuse in the category of psychostimulants, and for methylphenidate (MPH), a drug used for treating attention deficit hyperactivity disorder (ADHD), which can also be a psychostimulant drug of abuse. Other drugs of abuse such as nicotine, ethanol, heroin and morphine interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 243 publications
(409 reference statements)
3
81
0
Order By: Relevance
“…DAT at the cell surface is distributed between oligomers and monomers, where DAT monomers are internalized (Zhu and Reith) after amphetamine (51). Consistent with this idea, data Fleckenstein and co-workers (52) suggest the possibility that methamphetamine induces oligomerization of the transporter, whereas, a report by Reith group has shown that amphetamine promotes the formation of DAT monomers (55).…”
Section: Discussionmentioning
confidence: 75%
“…DAT at the cell surface is distributed between oligomers and monomers, where DAT monomers are internalized (Zhu and Reith) after amphetamine (51). Consistent with this idea, data Fleckenstein and co-workers (52) suggest the possibility that methamphetamine induces oligomerization of the transporter, whereas, a report by Reith group has shown that amphetamine promotes the formation of DAT monomers (55).…”
Section: Discussionmentioning
confidence: 75%
“…DATs are highaffinity targets for cocaine and amphetamine, both of which are highly addictive and widely abused substances (Zhu and Reith, 2008). Clinical studies using positron emission tomography have found that HIV-1-infected patients with HIV-1-associated dementia display a significant reduction in DAT density in the putamen and ventral striatum (Wang et al, 2004;Chang et al, 2008).…”
mentioning
confidence: 99%
“…It consists of 60 amino acids. When tyrosine is replaced with cysteine in DAT protein it results in decrease uptake of dopamine [67]. R290I: Arginine is replaced with isoleucine at position 290.…”
Section: Discussionmentioning
confidence: 99%